1974
DOI: 10.1021/j100595a006
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectra and reactivities of radical anions of 4-nitrobenzyl compounds produced by pulse radiolysis of acetonitrile solutions

Abstract: Electronic absorption spectra are reported for transients formed on pulse radiolysis of acetonitrile solutions of aromatic nitrobenzyl compounds and are assigned to the solute radical anions. Decay of the transients is fairly rapid but is markedly slower in the presence of tetraethylammonium formate. It is suggested that the CH2CN radical is responsible for the rapid decay and that formate ion scavenges this species. With 4-nitrobenzyl chloride, the decay of the transient is observed to be second order, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Pulse radiolysis of CH 3 CN results in the formation of solvated electrons, e s – , solvent radicals, • CH 2 CN, and protons (eq ) . Since e s – is a strong reducing agent, rapid one-electron reduction of a dissolved solute ensues. , In the presence of formate anion, it has been shown that the oxidizing side product, • CH 2 CN can be scavenged via hydrogen atom transfer, resulting in the production of a second reducing equivalent, CO 2 •– , as shown in eq . In principle, this should result in a net doubling of the yield of the one-electron reduced (OER) solute (eq ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse radiolysis of CH 3 CN results in the formation of solvated electrons, e s – , solvent radicals, • CH 2 CN, and protons (eq ) . Since e s – is a strong reducing agent, rapid one-electron reduction of a dissolved solute ensues. , In the presence of formate anion, it has been shown that the oxidizing side product, • CH 2 CN can be scavenged via hydrogen atom transfer, resulting in the production of a second reducing equivalent, CO 2 •– , as shown in eq . In principle, this should result in a net doubling of the yield of the one-electron reduced (OER) solute (eq ).…”
mentioning
confidence: 99%
“…, as shown in eq 6. 11 In principle, this should result in a net doubling of the yield of the one-electron reduced (OER) solute (eq 7). Further details of these processes are provided in the SI.…”
mentioning
confidence: 99%
“…However, methyl p -nitrophenyl sulfide shows a large deviation from the experimental value. This deviation can be accounted for with the role of this nitro compound as the electron acceptor for the excited state [(Ru)(terpy)(bpy)] 2+ component. The transient derived from the nitro compound after accepting an electron from the excited state Ru(II) complex has absorption in the wavelength range 500–550 nm. , Thus, the species, the nitro aromatic anion radical and sulfide cation radical, both contribute to the concentration of the species with the absorption maxiumum at 500–550 nm. Thus, the larger experimental rate constant obtained with methyl p -nitrophenyl sulfide is due to formation of two different transients with absorption in the similar wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…100−103 The transient derived from the nitro compound after accepting an electron from the excited state Ru(II) complex has absorption in the wavelength range 500− 550 nm. 100,102 Thus, the species, the nitro aromatic anion radical and sulfide cation radical, both contribute to the concentration of the species with the absorption maxiumum at 500−550 nm. Thus, the larger experimental rate constant obtained with methyl p-nitrophenyl sulfide is due to formation of two different transients with absorption in the similar wavelength.…”
Section: Transient Absorption Spectral Studiesmentioning
confidence: 99%
“…In principle, pulse radiolysis offers a convenient method for generating radical ions and excited states or preferentially one of them, depending on the solvent used and the saturating gas. For instance, acetonitrile was used for the pulse radiolytic generation of radical cations as well as radical anions derived from the appropriately chosen solutes. Pulse irradiation of neat acetonitrile leads to the formation of acetonitrile positive ions and classical solvated electrons (dipole-bound excess electrons) in dynamic equilibrium with dimeric radical anions (CH 3 CN) 2 •– (valence-bound excess electrons). Therefore, in this solvent saturated with Ar, both radical ions of the solute can be formed, whereas in O 2 -saturated acetonitrile, only radical cations are formed. On the other hand, 2-propanol was used for selective pulse radiolytic generation of radical anions derived from the solutes. ,, In this polar protic solvent, radical anions are formed through the attachment of the solvated electrons (e solv – ) to the solute molecule.…”
Section: Introductionmentioning
confidence: 99%